Using bibliotherapy to assist people to recover from depression in Thailand: Relationship between resilience, depression and psychological distress. Issue 6 (12th March 2014) - Songprakun, Wallapa; McCann, Terence V
Abstract : Thailand is experiencing a marked increase in the prevalence of depression. Self‐help has an important role in helping people with depression. The aim of this study was to assess if a favourable relationship existed between resilience, depression and psychological distress in participants with depression who receive bibliotherapy in comparison with a control group. A randomized controlled trial was conducted with 56 participants with moderate depression. The intervention group received the self‐help manual, whereas the control group received standard care. The findings showed a positive relationship between higher levels of resilience and lower levels of depression and psychological distress in the intervention group only, between baseline and posttest. The findings provide preliminary evidence supporting the use of bibliotherapy for individuals with depression in Thailand. Bibliotherapy can be incorporated easily into mental health nurses and other clinicians' work in promoting recovery in people with depression in the community.